2009
DOI: 10.1158/0008-5472.can-09-0945
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Concentration-Dependent Effects of the Polo-like Kinase 1–Specific Inhibitor GSK461364A, Including Differential Effect on Apoptosis

Abstract: Polo-like kinase 1 (Plk1) is a conserved serine/threonine kinase that plays an essential role in regulating the many processes involved in mitotic entry and progression. In humans, Plk1 is expressed primarily during late G 2 and M phases and, in conjunction with Cdk1/cyclin B1, acts as master regulatory kinases for the myriad protein substrates involved in mitosis. Plk1 overexpression is strongly associated with cancer and has been correlated with poor prognosis in a broad range of human tumor types. We have i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 46 publications
5
92
0
1
Order By: Relevance
“…In contrast, accumulation of aberrant spindles was observed following treatment with TAK-960 at 10 or 30 nmol/L. At 100 nmol/L or more concentration, the appearance and distribution of phenotypes consisted of monopolar spindles with characteristic polo spindle morphology (15).…”
Section: Tak-960 Mechanism Of Actionmentioning
confidence: 87%
“…In contrast, accumulation of aberrant spindles was observed following treatment with TAK-960 at 10 or 30 nmol/L. At 100 nmol/L or more concentration, the appearance and distribution of phenotypes consisted of monopolar spindles with characteristic polo spindle morphology (15).…”
Section: Tak-960 Mechanism Of Actionmentioning
confidence: 87%
“…Gilmartin et al found that GSK461364 caused lung carcinoma cells to arrest at prometaphase, and at lower concentrations, mitotic cells exhibited abnormal spindles and chromatins that could not be arranged on the equatorial plate. At higher concentrations, a monopolar spindle was formed and the chromatin decondensed around the monopolar spindle [25]. Another study reported that null-Plk1 led to the activation of SAC which was arrested at the prometaphase stage, thus showing developmental defects in zebrafish embryonic cells [2].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Several inhibitors of its catalytic activity are developed and some of them have proceeded to clinical trials. 9,10 We established a screening system for the inhibitors of PBD-dependent binding. 11 In this system, the open reading frame of a green fluorescent protein (GFP) is fused to PBD and expressed in bacteria.…”
mentioning
confidence: 99%